2008
DOI: 10.4161/psb.3.10.6643
|View full text |Cite
|
Sign up to set email alerts
|

Can Nep1-like proteins form oligomers?

Abstract: Nep1-like proteins (NLPs) are a novel family of microbial elicitors of plant necrosis that induce a hypersensitive-like response in dicot plants. The spatial structure and role of these proteins are yet unknown. In a paper published in BMC Plant Biology (2008; 8:50) we have proposed that the core region of Nep1-like proteins (NLPs) belong to the Cupin superfamily. Based on what is known about the Cupin superfamily, in this addendum to the paper we discuss how NLPs could form oligomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Previous reports raised the issue that NLPs may form oligomers in solution, especially dimers [23] , [31] . Additionally, it is well established that upon WBD progression, MpNep2 rather than MpNep1 accumulates in infected tissues, reaching its maximum concentration at the advanced necrotic stage [20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports raised the issue that NLPs may form oligomers in solution, especially dimers [23] , [31] . Additionally, it is well established that upon WBD progression, MpNep2 rather than MpNep1 accumulates in infected tissues, reaching its maximum concentration at the advanced necrotic stage [20] .…”
Section: Discussionmentioning
confidence: 99%
“…The oligomeric profile of MpNep2 has not been studied previously. Cechin and colleagues [31] discussed how NLPs could form oligomers based on sequence and structural similarities to the Cupin superfamily, a diverse group of proteins containing a conserved barrel domain known as cupa . MpNep2 protein was believed to act primarily in biotrophic mycelia as a monomer.…”
Section: Discussionmentioning
confidence: 99%
“…NEP1-like proteins (NLPs) occur in oomycetes, fungi, and bacteria and induce a hypersensitive-like response in a large number of dicotyledonous plants [2][3][4][5][6]. The 3D-structure of the NLPs remains to be determined experimentally, however recent bioinformatics studies have suggested that they belong to the Cupin superfamily [7,8]. NLPs seem to have a significant role in pathogenicity and these proteins may contribute to virulence since they are prevalent especially in plant pathogenic organisms (review in Ref.…”
Section: Introductionmentioning
confidence: 99%